EMANCIPAÇÃO POLÍTICA E EDUCAÇÃO: AÇÕES EDUCACIONAIS PARA O IDOSO NAS INSTITUIÇÕES DE ENSINO SUPERIOR PÚBLICAS PARANAENSES - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Capitalist society is marked by social contrasts, educational, economic and political. Reproduction of this sociability and the dominant ideology marks the dominated class, which affects the sale reflects the marginalization and vulnerability of the subject. Emana the need to emancipate the subject, to be aware of the society in which it appears and moves that enable the transformation. In the current social model, we can achieve political emancipation through a training action with emancipatory principles. Education enables the questioning of reality and the instrumentalization from knowledge. In this context we observe the situation of the elderly, such as the difficulties he faced. Discussions about aging are in evidence, since this is a global trend. In Brazil there are 25 million seniors (IBGE, 2013). Although a significant number, there are still prejudices through a negative stereotype of old age. Although they have been implemented public directed to the elderly policies (welfare, health, nutrition and educational processes), in practice have not been guaranteed its effectiveness, however, among the actions prescribed in the Elderly, it highlights the importance of higher education institutions offer educational activities for the elderly which have spread throughout the country. This research is characterized as qualitative, being grounded from the materialist dialectic, and has as its object the educational activities for the elderly developed by projects / courses in Public Institutions of Higher Education Paranaenses. It appears as problematic: The educational programs for the elderly developed by projects / courses Public Paranaenses higher education institutions fulfill their educational function and contribute to political emancipation of the elderly? The objective of the research is to analyze the educational activities for the elderly developed by projects / courses in Public Higher Education Institutions Paranaenses as strategies for political emancipation of the elderly, founded on the concept of lifelong education. The thesis is defended: Educational actions developed by Paraná public IHE through UATI, fulfill their educational function and contribute to the political emancipation of the elderly. The research is based on Furter (1976), Gadotti (1984, 2012), Konder (2009), Marx (2006, 2009, 2011), Mészáros (2006, 2008), Oliveira (1998, 1999) and Tonet (2012, 2013 ). For data collection were questionnaires with open and closed questions for the elderly of the Open University for the Third Age of the state's public higher education institutions, totaling 146 subjects from 7 institutions: UEPG (19 seniors), UNESPAR / Paranagua (18), UNICENTRO / Irati (19), UNICENTRO / Guarapuava (20), UNIOESTE / Foz do Iguaçu (16), UEM (22) and UFPR (32). Questionnaires were applied with open and closed questions for teachers of UATI, totaling 25 subjects 6 educational activities. The teachers of an institution did not respond to the questionnaire. There was also the questionnaires with open and closed questions for the coordinators. 7 of the coordinators of the UATI of the state's public higher education institutions, 5 answered the questionnaire. As a result the research shows that the educational activities for the elderly aim emancipatory processes, even though they have no such name on your goals. Developed work enable the upgrade, self-esteem increase, improvement in quality of life and social inclusion of the elderly. Even with limitations, education for seniors contributes to the awareness of the elderly, can be glimpsed political emancipation from the dialectical relationship between education, man and society.
Emancipação política e educação: ações educacionais para o idoso nas Instituições de Ensino Superior públicas paranaenses
Keywords: Emancipação política; Educação; Educação permanente; Idoso; Universidade Aberta para a Terceira Idade; Emancipation policy; Education; Continuing education; Old man; Open University for the Third Age; CNPQ::CIENCIAS HUMANAS::EDUCACAO